Pelatihan Produksi Eco-Enzyme Dari Limbah Organik Bagi Masyarakat Sapanang Kecamatan Bungoro Kabupaten Pangkep - Pratiwi, Diana Eka; Djangi, Muh. Jasri; Jumrah, Elfira (Program Studi Manajemen FEB UNM, 2026)
Household organic waste remains a significant environmental challenge in Indonesia due to limited public awareness and skills in proper waste management. One practical solution is the utilization of organic waste into eco-enzyme, which has both functional and economic value. This Community Service Program (PKM) aimed to improve the knowledge and skills of the community in producing eco-enzyme from organic waste in Sapanang Village, Bungoro District, Pangkep Regency. The implementation methods included socialization, training, hands-on practice, mentoring, and evaluation stages. Evaluation was conducted using pre-test and post-test analyzed through the N-Gain method. The results showed a very high level of participant engagement, with 100% attendance throughout the activities. In addition, there was a significant improvement in participants’ understanding, indicated by an N-Gain score of 0.641 in the moderate category. Participants were able to independently practice eco-enzyme production and understand the indicators of successful fermentation. Continuous mentoring also helped participants overcome technical challenges and maintain consistency in household-level practices. Therefore, this training program proved effective in enhancing community awareness, knowledge, and skills in environmentally friendly organic waste management, while also providing potential opportunities for community-based economic empowerment